Design, metallurgical features, mechanical performance and canal preparation of six reciprocating instruments. (5th May 2021) - Martins, J. N. R.; Silva, E. J. N. L.; Marques, D.; Belladonna, F.; Simões‐Carvalho, M.; Vieira, V. T. L.; Antunes, H. S.; Braz Fernandes, F. M. B.; Versiani, M. A.
Abstract: Aim: To compare six reciprocating instruments regarding their geometric design, metallurgical characteristics, mechanical behaviour and ability to prepare root canals. Methodology: A total of 246 new 25‐mm NiTi instruments (41 per group) from six reciprocating systems (Reciproc, Reciproc Blue, One Files, One Files Blue, Reverso Silver, and WaveOne Gold) were evaluated throughout a multimethod approach regarding their design using stereomicroscopy (number of blades and helix angle) and scanning electron microscopy (blades symmetry, cross section and surface finishing), nickel‐titanium composition, phase transformation temperatures, mechanical performance (cyclic fatigue, torsional and bending resistance) and unprepared canal surface area on anatomically matched mandibular molars assessed by micro‐CT. One‐way ANOVA and post hoc Tukey's or Mood's median tests were selected depending on sample distribution with significance level set at 5%. Results: The instruments had similarities regarding their metal composition and unprepared canal area, whilst differences in phase transformation temperatures and geometric design (number of blades, surface finishing and tip geometry) were observed. Overall, no difference was observed regarding the maximum torque values ( P  > 0.05), whilst One Files (72 s) and One Files Blue (414 s) had the shortest and longest times to fracture, respectively ( P  < 0.05). Similar angles of rotation were observed in Reciproc (310°), One Files (285°) and Reverso Silver (318°) instruments ( P  > 0.05), which were significantly lower than Reciproc Blue (492°), One Files Blue (456°) and WaveOne Gold (492°; P  < 0.05). Maximum bending load demonstrated that Reciproc Blue (201.3 gf) was significantly more flexible that the other instruments ( P  < 0.05). Conclusion: Although there were similarities in metal composition and percentage of unprepared canal surface, the instruments had differences in the overall geometric design, phase transformation temperatures and in the four mechanical resistance parameters (time to fracture, maximum torque, angle of rotation and maximum bending load).